BAHASA RITUAL BALI SEBAGAI REPRESENTASI IDENTITAS KULTURAL: PENDEKATAN ANTROPOLOGI LINGUISTIK - Pande Gede Brahmandika (Yayasan Pendidikan Literasi Borneo, 2025)
This study examines Balinese ritual language as a representation of cultural identity through a linguistic anthropological approach. Qualitative methods were used, including observation, interviews, and documentation studies of ritual practices and religious palm-leaf manuscripts. The results indicate that ritual language has a transcendental function, connecting humans with divine powers, and a social function in strengthening community solidarity. Its linguistic structure is characterized by repetitive formulas, sacred script, and Sanskrit vocabulary that reflect Hindu-Balinese cosmology. However, globalization and declining interest among the younger generation pose challenges to the transmission of ritual language. Therefore, preservation is necessary through formal education and the role of indigenous communities to ensure that ritual language remains alive as a religious heritage and cultural identity of the Balinese people